Within-person methodology to study the addiction recovery process of women. Issue 2 (3rd April 2022) - Apsley, Hannah B.; Cross-Ramirez, Marci; Miller, Sara E.
Abstract: Women are among the fastest growing populations of those with substance use disorders in the United States. Women face different social barriers than men in their access to treatment and recovery from these disorders. Differentially experienced barriers include greater child caregiving responsibilities, social sigma regarding motherhood and substance use, romantic partners who also use substances, experiences of violence and trauma, and, relatedly, symptoms of post-traumatic stress disorder. These barriers have been studied primarily by employing between-group approaches (e.g. comparing men and women) or between-persons approaches (e.g. cross-sectionally assessing the relationship between person-level PTSD symptoms and relapse). However, there are limited studies on women's gender-specific experiences in recovery with the aim of elucidating within-person effects. Employing within-person designs, such as daily diary or ecological momentary assessments, has many advantages. These advantages include reducing retrospective bias, assessing temporality of processes that occur on a short time scale, and analyzing processes that may occur when individuals deviate from their personally normative experiences. Studying women's experiences in recovery "as they are lived" will enable the development of interventions that are fine-tuned to the specific needs of each woman, and ultimately may help to reduce the suffering of women with substance use disorders.